What are the position and power of supermarkets in the Australian food system, and the implications for public health? A systematic scoping review - Pulker, Claire; Trapp, G.; Scott, Jane; Pollard, Christina (Wiley-Blackwell Publishing Ltd., 2018)
© 2017 World Obesity Federation. Supermarkets have been described as having unprecedented and disproportionate power in the food system. This scoping review synthesized the literature that describes the position and power of supermarkets in the Australian food system, and the implications for public health. A systematic search of peer-reviewed and grey literature identified 68 documents that described supermarket power. Implications for public health were also recorded. Data revealed that supermarkets hold a powerful position in the Australian food system, acting as the primary gatekeepers. Supermarkets have obtained instrumental, structural and discursive power from many sources that overlap and reinforce each other. Few positive public health impacts of supermarket power were identified, providing many opportunities for improvement in the domains of food governance, the food system and public health nutrition. There is very little public health research examining the impact of supermarket power in Australia. More research is needed, and examination of supermarket own brands is of particular importance owing to their pivotal role as a source of power and their potential to improve public health outcomes, such as obesity.